Analysis of the Occurrence of Critical Thinking in Biology Teaching Modules on Enzymes Class XII High School in Surakarta - Putri, Rinanda Arini; Hariyatmi, H (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Critical thinking skills are very important in learning biology which emphasizes on providing direct learning experiences by developing thinking skills. The study of biology requires problem solving skills through critical thinking. The purpose of this study was to analyze the emergence of critical thinking in the biology teaching module of high school enzyme material in Surakarta. The type of research included descriptive qualitative. The population in this study were all biology teachers in Surakarta. The sample was 15 high school biology teachers in Surakarta, one teacher each per school (Public, Private, Muhammadiyah). Sampling was done purposively with each school analyzed 5 teaching modules. Data collection techniques by means of documentation and interviews and then the data were analyzed descriptively. The results showed that the emergence of critical thinking in each indicator was different for State, Private and Muhammadiyah schools. Thus, the conclusion that can be put forward is that the highest occurrence of critical thinking is in private school teaching modules (35.37%), with the most frequently appearing indicator being giving simple explanations (45.33%) and the least frequently appearing tactical strategies (2.67%). These findings can provide information to high school biology teachers regarding critical thinking strategy and tactics indicators.